Evaluating Future Automation Work in Process Plants with an Experience-Driven Science Fiction Prototype - Kymalainen, Tiina; Kaasinen, Eija; Aikala, Maiju; Hakulinen, Jaakko; Heimonen, Tomi; Paunonen, Hannu; Ruotsalainen, Jouni; Lehtikunnas, Lauri; Mannonen, Petri (Proceedings (International Conference on Intelligent Environments), 2016)
This paper introduces a video-illustrated science fiction prototype "Remote operator's day in a future control center in 2025" aimed at discovering opportunities for new interaction methods and smart automation for the future factories of Industry 4.0. The theoretical objective was to carry out experience design research in an industrial work context based on explicit user experience (UX) goals. This paper firstly describes how the nominated UX goals were implemented in a video-illustrated science fiction prototype and, secondly, how the prototype was evaluated in two research setups: as video sequences embedded in a Web survey, and as interviews carried out with process control workers. The main contribution is to demonstrate how the science fiction prototyping method can employ video-illustration as a means for future-oriented UX research, and how complementary user-centered methods may be used for validating UX goals by means of a science fiction prototype.